Human‐facilitated dispersal of the Gulf toadfish Opsanus beta (Goode & Bean, 1880) in the Guaratuba Bay, south‐eastern Brazil. Issue 3 (27th July 2020) - de Carvalho, Barbara M.; Ferreira Junior, Augusto L.; Fávaro, Luís F.; Artoni, Roberto F.; Vitule, Jean
Abstract: Opsanus beta is endemic to the Gulf of Mexico and has recently been introduced to the Brazilian coast; probably the introduction is via ballast water and/or oil rigs. In this study, the presence of the species is recorded for the first time in Guaratuba Bay, on the southern coast of Brazil. In this region there are no port terminals, which suggests that O. beta used a different mode of human‐facilitated transport to colonize Guaratuba Bay.